Formação e trabalho do coordenador pedagógico na Secretaria Municipal de Educação de São Paulo (1985-2021) - Silva, Juliana Prezia e (2024)
The field of Pedagogy has historically sought to deepen the debate about teacher education. Within this context, a specific focus has gained relevance associated with the pedagogical coordinator, a professional who has increasingly been included in educational policies, particularly since the 1980s. This research focuses on the process of training pedagogical coordinators as teachers' trainers in the São Paulo City Hall. The aim was to investigate how the work with these professionals has been shaped in official documents, from 1985 to 2021, specifically in publications from the São Paulo Municipal Secretary, with a focus on their role in teacher education. It involves an analysis of the themes and proposals of training materials and publications directed at coordinators, from general documents to lectures and specific activities, which establish the foundations and conceptions for their training dimension. The research aims for a critical dialogue with the political period of the literature prescribing the nature of this professional's work, such as Almeida and Placco (2009) who organize the work of the pedagogical coordinator into three dimensions: "trainer, articulator, and transformer," and Roger Chartier (1988), who addresses representations to discuss how cultural goods convey intentions associated with different positions of power individuals occupy in society. The research reveals the different representations of the pedagogical coordinator as a teacher trainer throughout administrations, showing who they truly serve